Religion today : a critical thinking approach to religious studies - Aden, Ross, 1946- (Rowman & Littlefield Publishers, 2013)
Religion Today introduces students to key concepts in religious studies through a compelling problem-solving framework. Each chapter opens with a contemporary case study that helps students engage in current religious issues, explore possible solutions to difficult religious problems today, and learn key themes and concepts in religious studies.